αII-Spectrin Breakdown Products (SBDPs): Diagnosis and Outcome in Severe Traumatic Brain Injury Patients - Mondello, Stefania; Robicsek, Steven A.; Gabrielli, Andrea; Brophy, Gretchen M.; Papa, Linda; Tepas, Joseph; Robertson, Claudia; Buki, Andras; Scharf, Dancia; Jixiang, Mo; Akinyi, Linnet; Muller, Uwe; et al. (Journal of neurotrauma, 2010)
In this study we assessed the clinical utility of quantitative assessments of alphaII-spectrin breakdown products (SBDP145 produced by calpain, and SBDP120 produced by caspase-3) in cerebrospinal fluid (CSF) as markers of brain damage and outcome after severe traumatic brain injury (TBI). We analyzed 40 adult patients with severe TBI (Glasgow Coma Scale [GCS] score <or=8) who underwent ventriculostomy. Patients requiring CSF drainage for other medical reasons served as controls. CSF samples were taken at admission and every 6 h thereafter for a maximum of 7 days and assessed using novel quantitative fragment-specific ELISAs for SBDPs. Outcome was assessed using the 3-month Glasgow Outcome Scale. Mean CSF levels of SBDPs were significantly higher in TBI patients than in controls at all time points examined. Different temporal release patterns of CSF SBDP145 and SBDP120 were observed. SBDP145 provided accurate diagnoses at all time points examined, while SBDP120 release was more accurate 24 h after injury. Within 24 h after injury, SBDP145 CSF concentrations significantly correlated with GCS scores, while SBDP120 levels correlated with age. SBDP levels were significantly higher in patients who died than in those who survived. SBDP145 levels (>6 ng/mL) and SBDP120 levels (>17.55 ng/mL) strongly predicted death (odds ratio 5.9 for SBDP145, and 18.34 for SBDP120). The time course of SBDPs in nonsurvivors also differed from that of survivors. These results suggest that CSF SBDP levels can predict injury severity and mortality after severe TBI, and can be useful complements to clinical assessment.